Autoritarismo, populismo e liberdade de expressão no Brasil: a censura à imprensa a partir de 2019. - Valença, Natalia Bezerra (2022)
Have populist attacks on journalists represented a form of press censorship in Brazil since 2019? The present dissertation seeks to answer this research question, through the investigation of the attacks on the press, promoted by the Government of the President of the Republic Jair Bolsonaro since its inauguration in 2019, verifying if this posture has resulted in the weakening of the freedom of the press and represented a way to create barriers and censor opponents of the Government. The central hypothesis for the problem presented is that the confrontation with press activity in Brazil, during the Bolsonaro government, has reduced democratic pluralism and has represented forms of censorship and barriers to opponents. Freedom of the press and democratic pluralism are some of the bases of constitutional democracy formed after the Federal Constitution of 1988. From these bases arise several other rights, such as the right to information for the formation of opinion, as well as fundamental political rights to maintain one's own democracy. The control of information and the formation of consensus can be a mechanism for maintaining authoritarian governments, with censorship being one of the instruments that makes it possible to silence political opponents. The present research was developed from the use of qualitative empirical methodology, with bibliographic survey on populism, democratic constitutionalism, freedom of the press and censorship in Brazil. In addition, a case study was carried out from the context of the global recession of constitutional democracy and the rise of new digital media, with an analysis of the repercussions in Brazil from 2019 onwards.